Spatial Game Signatures for Bot Detection in Social Games - Barik, Titus; Harrison, Brent; Roberts, David; Jiang, Xuxian (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
Bot detection is an emerging problem in social games that requires different approaches from those used in massively multi-player online games (MMOGs). We focus on mouse selections as a key element of bot detection. We hypothesize that certain interface elements result in predictable differences in mouse selections, which we call spatial game signatures, and that those signatures can be used to model player interactions that are specific to the game mechanics and game interface. We performed a study in which users played a game representative of social games. We collected in-game actions, from which we empirically identified these signatures, and show that these signatures result in a viable approach to bot detection. We make three contributions. First, we introduce the idea of spatial game signatures. Second, we show that the assumption that mouse clicks are normally distributed about the center of buttons is not true for every interface element. Finally, we provide methodologies for using spatial game signatures for bot detection.